Analisa Penggunaan Bahan Bakar Bioetanol Dari Limbah Kertas Sebagai Bahan Bakar Genset - Hartantio, Yoppy; Hartati, Rukmi Sari; Kumara, I Nyoman Satya (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2018)
The high fuel demand in Indonesia has resulted in an increase in the ratio of imported fuels and weakened domestic energy security. In response to this, biofuels (BBN) was developed, one of which was bioethanol. The raw material for making bioethanol can be from a variety of objects, but paper is the most easily obtained bioethanol raw material around us. PT Temprina Media Grafika a subsidiary of Jawa Pos Group produces waste paper every day. From the waste is processed into bioethanol and is used as a generator fuel. From 1 kg of paper waste obtained 30 ml of bioethanol with a concentration of 86%. By mixing bioethanol in gasoline, a mixture of fuels called E85, E60 and E35 is obtained. While pure RON 88 gasoline from Pertamina is called E10. Through testing on the generator set with a load of 600 watts and 900 watts, measurements of voltage, power, frequency, RPM and SOFC were obtained that all parameters decreased when using bioethanol mixed fuels.